Pre-Vitrification Artificial Shrinkage Mitigates the Cryo-Injury When Biopsied Blastocysts are Already Re-Expanding - Tetsuya Miki; Kenji Ezoe; Mariko Aruga; Mika Narisawa; Nanoha Fujiwara; Megumi Ibayashi; Satoshi Ueno; Tadashi Okimura; Yoshikazu Nagao; Keiichi Kato (Fertility & Reproduction, 2025)
Introduction: Vitrifying blastocysts immediately after trophectoderm biopsy is recommended in clinical settings. However, in some cases, embryologists cannot perform vitrification immediately after biopsy because of other tasks, during which the blastocysts may begin to re-expand. Aims: This study aimed to investigate whether artificial shrinkage (AS) before vitrification affects adhesion capabilities and outgrowth competence of biopsied blastocysts with various re-expansion degrees. Methods: In total, 225 vitrified human blastocysts donated for research by consenting couples were used. Biopsied blastocysts were vitrified at 0–3 hours post-biopsy. The re-expansion degree (%) just before vitrification was calculated using the blastocyst diameter post-biopsy (Db), diameter just before vitrification (Dv), and intra-zona pellucida diameter (Dz) according to the following formula: (Dv - Db)/(Dz - Db) × 100. The blastocysts were categorized according to re-expansion degree as Expansion I, [Formula: see text] 0%; Expansion II, 1%–49%; Expansion III, 50%–99%; and Expansion IV, [Formula: see text]100%. Some blastocysts were artificially shrunk in hypertonic solution before vitrification. Correlations among outgrowth outcomes, re-expansion degree, and AS were examined. Results: Multivariate linear regression analysis demonstrated that the blastocyst outgrowth area was significantly smaller in the Expansion III group ([Formula: see text] = 0.0134). The outgrowth area in the Expansion III group was recovered by AS before vitrification ([Formula: see text] = 0.0103) and was comparable to those observed in the Expansion I, II, and IV groups. Conclusions: The outgrowth competence was adversely affected when blastocysts were vitrified during the late re-expansion period; however, this adverse effect was mitigated by pre-vitrification AS. Our findings may contribute to the improvement of day-to-day practices in embryology laboratories.